Técnicas de lectura y su incidencia en la comprensión lectora en estudiantes de décimo año de educación General básica, área de Lengua y Literatura del Colegio Atahualpa de Machala 2013-2014. - Cabezas Jaramillo, Ronny Cássidy (2014)
In this one, the activities of each technique of reading, as well as tasks directed to students of Tenth Year are described. In addition, reading comprehension is described detailing the levels of measurement, their development and their importance in the teaching process.